A DESIGN OF SMART PLANT ROBOTS BASED ON ARTIFICIAL NEURAL NETWORK - Frans Erwinsyah Simaremare; Solly Aryza; Hamdani Hamdani (INFOKUM, 2022)
Robots had always been studied in various areas for educational, medical, and military purposes. However, in various writings, the manufacture of robots that are applied in plantation practice is very low. In this research, a robot for automatic watering has been developed. because the water circulation in Indonesia will run low, and when watering plants really need a lot of water and sometimes it is wasted as well as spending time applying it. Therefore, this research is applied research that can be applied in plantations.